Estimating the Nexus of Tourism on Sustainable Development Goals in Nigeria - Oguchi, Ngozi Helen; Luo, Fen (Technium Social Sciences Journal, 2021)
Tourism industry has become one of the principal sources of economic growth and a viable platform of employment both in Africa and globally. Considering that economic growth and job creation are the focal points of sustainable development goals (SDGs), this study is focused on investigating the relationship they have with tourism in Nigeria. A gross domestic product (GDP) time series dataset is utilized to represent economic growth variable while, statistical data obtained from the WTTC is employed to denote Tourism revenues and arrivals in Nigeria. The study employed Autoregressive Distributed Lag (ARDL) bounds test of cointegration, the Error Correction model and Granger causality tests to empirically examine the impacts tourism has on economic growth and employment in the LACKET states of Nigeria for the period between 1999 to 2019. Generally, the investigations indicate that both in the short - and long - run, tourism is positively related to economic growth and employment rate in Nigeria. However, regarding short -run relationship, a lower positive link of tourism revenue is recorded.